The Influence of Customer Experience and Brand Image on Customer Satisfaction (Study of Tokopedia users in Bandung) - Zulganef, Zulganef; Taruna, Dicky Gustafianto (DeReMa (Development Research of Management): Jurnal Manajemen, 2024)
This study aims to analyze customer satisfaction for Tokopedia users in Bandung City. This study uses the variables customer experience and brand image to analyze the effect of these variables on customer satisfaction for Tokopedia users in Bandung City. Respondents in this study totaled 106 people. The sampling technique used is purposive sampling technique through questionnaire. The data analysis used is the instrument test of validity, reliability, classical assumption  test,  descriptive  analysis method  and  multiple  linear regression  analysis. This research results found that the customer experience and brand image variables have a positive effect on customer satisfaction.  Authors also make some recommendation Abstrak dalam Bahasa Indonesia.Penelitian ini bertujuan untuk menganalisis Kepuasan Pelanggan pengguna Tokopedia di Kota Bandung. Penelitian ini menggunakan variabel Pengalaman Pelanggan dan Citra Merek untuk menganalisis pengaruh variabel-variabel tersebut terhadap Kepuasan Pelanggan pengguna Tokopedia di Kota Bandung. Responden dalam penelitian ini berjumlah 106 orang. Teknik pengambilan sampel yang digunakan adalah purposive sampling melalui kuesioner. Analisis data yang digunakan meliputi uji instrumen validitas, reliabilitas, uji asumsi klasik, metode analisis deskriptif, dan analisis regresi linier berganda. Hasil penelitian ini menunjukkan bahwa variabel pengalaman pelanggan dan citra merek memiliki pengaruh positif terhadap kepuasan pelanggan. Penulis juga memberikan beberapa rekomendasi.